Tinjauan Literatur Tentang Pengaruh Budaya Organisasi Terhadap Kinerja Karyawan - Fahrani Adisa; St Rahma Aminuddin; Nur Asifa; Yurmila Maria Nura; Chris Dayanti Br. Ginting (Program Studi Pendidikan Akuntansi, Fakultas Ekonomi, Universitas Negeri Makassar, 2025)
This study aims to review various literature discussing the effects of organizational culture on employee Performance. Organizational culture refers to the values, beliefs, and norms that guide behavior in the workplace. From the literature review, it was found that a strong, positive, and adaptive organizational culture can enhance employee motivation, loyalty, and productivity. Conversely, a weak organizational culture can lower work motivation and individual achievement. This article emphasizes the importance of management's role in fostering an organizational culture focused on performance, collaboration, and innovation to achieve the company's goals sustainably.